Death from salt and baking soda ingestion. Issue 1 (1st January 2020) - Mehlenbacher, Gabrielle; Garbach, David; Eggleston, William; Gorodetsky, Rachel; Nacca, Nicholas
Abstract: Table salt (sodium chloride) and baking soda (sodium bicarbonate) are rarely included on the list of potentially dangerous household toxins and many clinicians are unfamiliar with the management of ingestion or overdose. Table salt overdose has been reported after attempted induction of emesis and improper preparation of infant formula. The latter have resulted in severe toxicity and death. Sodium bicarbonate use for the treatment of dyspepsia and in religious exorcism rituals has also been reported to cause severe toxicity and death. Specifically, large quantities of sodium chloride have been reported to cause hemodynamic instability, electrolyte abnormalities, seizures, altered mental status, cerebral edema, and thrombi secondary to red blood cell crenation. Acute ingestions of sodium bicarbonate have been reported to cause metabolic alkalosis, electrolyte abnormalities, altered mental status, dysrhythmias, tachypnea, and rhabdomyolysis. We report a case of ingestion of sodium chloride and sodium bicarbonate in an attempt to induce emesis, which resulted in death.